PWE-040 Natural History of Cirrhosis in A Cohort of Patients Undergoing Structured Surveillance for Hepatocellular Carcinoma: Results from The Aberdeen Surveillance Cohort. (17th August 2016) - Lalwani, S; Mukhopadhya, A; Fraser, A; Hold, GL; Bailey, L; Vijayan, B; English, S; Mcleman, L
Abstract : Introduction: Cirrhosis is the end-stage of chronic liver disease due to a variety of different aetiologies with the natural history of this condition characterised by a variable asymptomatic phase of compensation followed by a rapid 'decompensated' phase marked by ascites, jaundice, variceal bleeding, encephalopathy and development of hepatocellular carcinoma (HCC). The cornerstone of management for cirrhotic subjects includes 6 monthly surveillance to detect development of HCC. Aberdeen Royal Infirmary is one of the few centres in the UK to have a structured HCC screening program where patients are followed up in a nurse led clinic. The aim of this study was to determine rates of decompensation and development of HCC in a cohort of cirrhotic patients undergoing structured surveillance. Methods: The electronic records of 231 patients who were initiated on surveillance between the years 2010–2015 were reviewed. Only patients who attended the clinic on at least 2 occasions were included. Those with a prior history of HCC or had an HCC discovered at their first ultrasound were excluded. Primary end-points studied were the time to develop ascites, variceal haemorrhage, hepatic encephalopathy, jaundice, HCC and mortality. Data analyses were conducted using SPSS version 23. Statistical methods used include Cox regression and Kaplan Meier survival analyses. Results: The 231 patients included in the study were mostly male (61.5%) with alcohol being the predominant aetiological factor (33.3%). The mean age at entry into the cohort was 58.1± 11.2 years, with a mean MELD of 8.6±2.9 and UKELD of 48.2± 3.1. The median follow-up duration was 26 months (range 6–60) giving a total cohort follow up of 522 patient years. Most patients had compensated and Childs-Pugh A cirrhosis at the time of entry (62.8% and 60.2% respectively). Of the 145 patients with compensated cirrhosis at entry, 26 (19.9%) developed jaundice or other signs of decompensation during follow up. Mean time to first decompensation episode was 49 (95% CI; 45–52) months, giving a rate of 8.7 /100 patient years. During follow-up, 7 patients developed HCC giving a detection rate of 1.36/100 patient-years. Mean age at detection of HCC was 71.6 ± 7.3 years. Mortality rate in the entire cohort was 3.6/100 patient years. Conclusion: The results from our surveillance cohort outline the natural history of a large group of cirrhotic patients systematically followed up in a structured nurse-led clinic. The rates of decompensation and HCC highlight the importance of pursuing the strategy of active surveillance. Disclosure of Interest: None Declared